Geographical Distribution of Agricultural Crop Productivity Dependent on Modern Irrigation Methods in Al-Alam and Al-Dur Districts - Khadafy, Abdullah Khalid; Mohammed, Adnan Attia (Journal of Tikrit University for Humanities, 2023)
The impact of modern irrigation methods on the productivity of agricultural crops, as well as identifying the most important problems or effects facing the study area as a result of the excessive use of surface water in irrigated agriculture and its impact on the productivity of agricultural crops, lies the importance of using modern irrigation methods through increasing the productivity of crops grown in the study area. Several approaches were used for the study, including the inductive approach that starts from the part to the whole, and the technical approach, which extended the study with modern geographic techniques in analyzing satellite visuals, in addition to the quantitative approach and the analytical approach based on analyzing the title and content of the research and drawing results, and that the geographical distribution of modern irrigation methods will be dealt with In this research, the most important crops that are irrigated with modern irrigation techniques, the area of the study area reached (3911.24) km 2, while the arable area is (275,236) dunums, and the farm area actually reached (1,860,000) dunums. . Hence, their contributions to the agricultural planning process are almost limited, and this is not consistent with the importance assigned to the agricultural sector. The geographer finds himself in this field in front of an urgent need to contribute to studies related to water resources, methods and variations in agricultural production. Modern irrigation that helps to save water and increase the productivity of agricultural crops within the study area